Respuesta :
Answer:
The equation of the line passing through the points (-2,0) and (0,-4)
[tex] \frac{y - y1}{x - x1} = \frac{y2 - y1}{x2 - x1} [/tex]
[tex] \frac{y - 0}{x - ( - 2)} = \frac{ - 4 - 0}{0 - ( - 2)} = \frac{ - 4}{2} = - 2[/tex]
[tex]y = - 2(x + 2) \\ y = - 2x - 4[/tex]
[tex]2x + y = - 4[/tex]
The equation of the line passing through the points (0,-2) and (4,0)
[tex]\frac{y - y1}{x - x1} = \frac{y2 - y1}{x2 - x1} \: [/tex]
[tex] \frac{y - ( - 2)}{x - 0} = \frac{0 - ( - 2)}{4 - 0} [/tex]
[tex] \frac{y + 2}{x} = \frac{1}{2} [/tex]
[tex]x - 2y = 4[/tex]
Option B
x minus 2 y = 4 and 2 x + y = negative 4
The system of equation can be determine by using formula of equation of the line passing through the points [tex](x_1, y_1)[/tex] and [tex](x_2, y_2)[/tex].
The system equation would be [tex]2x+y=-4[/tex] and [tex]x-2y=4[/tex].
Given:
The given points are [tex](-2,0)[/tex] and [tex](0,-4)[/tex] and for another line [tex](0,-2)[/tex] and [tex](4,0)[/tex].
Find the equation line passing through point [tex](-2,0)[/tex] and [tex](0,-4)[/tex] .
[tex]\dfrac{y-y_1}{x-x_1}=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
Substitute the value in above equation.
[tex]\dfrac{y-0}{x-(-2)}=\dfrac{-4-0}{0-(-2)}\\y=-2(x+2)\\y=-x-4\\2x+y=-4[/tex]
Find the equation line passing through point [tex](0,-2)[/tex] and [tex](4,0)[/tex] .
[tex]\dfrac{y-y_1}{x-x_1}=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
Substitute the value in above equation.
[tex]\dfrac{y-(-2)}{x-0}=\dfrac{0-(-2)}{4-0}\\\\x-2y=4[/tex]
Thus, the system equation would be [tex]2x+y=-4[/tex] and [tex]x-2y=4[/tex].
Learn more about equation of line here:
https://brainly.com/question/2564656